Quantum Image Encryption and Decryption Algorithms Based on Quantum Image Geometric Transformations - Zhou, Ri-Gui; Wu, Qian; Zhang, Man-Qun; Shen, Chen-Yi (International journal of theoretical physics, 2013)
Cryptography is the essential subject for network information security to protect important data. Although following the symmetric cryptosystem for which the participations in the communication keep exactly the same keys, the special for the encryption and decryption algorithms proposed in this paper lays in the operational objectives, the quantum image. Firstly, extracts the properties of gray-scale and position from the quantum gray-scale image which the storage expression of image in quantum states is achieved. Along with the geometric transformations in classical images, this article realizes the quantum image geometric transforms by means of designing quantum circuits. Eventually, through a combination of the proposals in previous, the encryption and decryption algorithms on quantum gray-scale images is finally accomplished, which could ensure the confidentiality and security of the information in delivery. The algorithms belong to the application of quantum image geometric transformations, for further, the new explorations for quantum image cryptography researches.